Analisis Perputaran Modal Kerja Dan Perputaran Kas Terhadap Profitabilitas Pada UMKM Jahit Yurani Store - Rahayu, Sri; Rizal Gaffar, Mohammad (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Objective – This study aims to determine the effect of working capital turnover and cash turnover on the profitability of this business. Novelty – The novelty of this research lies in the sewing sector MSMEs with monthly data coverage for one full year, which has not been widely discussed by previous studies. In addition, the combination of working capital turnover and cash flow as independent variables on the profitability of small-scale MSMEs is an approach that has not been widely used in similar studies. Method – The quantitative approach used is multiple linear regression. The data studied comes from secondary sources, namely monthly financial reports selected using a purposive sample approach from February 2024 to February 2025. Destination –The results showed that profitability is influenced by working capital turnover and cash turnover simultaneously. Cash turnover does have a considerable influence on profitability, but capital turnover does not. Therefore, effective cash management is essential to maximize profits. Limitations and Implications – This research is limited to one sewing MSME unit, so the results cannot be generalized to all types of MSMEs. The implications of this research can be used by MSME actors in designing more effective financial strategies, as well as being taken into consideration for academics in developing similar research in the MSME sector.